2009
DOI: 10.1111/j.1460-9592.2009.03184.x
|View full text |Cite
|
Sign up to set email alerts
|

An acute pain service improves postoperative pain management for children undergoing selective dorsal rhizotomy

Abstract: Although we recognize that it is possible that there were changes in care not related specifically to the introduction of a dedicated APS that occurred in our institution that resulted in improvements in general postoperative care and in length of stay, our study did show that having an organized APS allowed to significantly decrease the incidence of postoperative oxygen desaturation and to decrease the hospital length of stay by 1 day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Regular assessment was significantly higher in APS/APMP hospitals, where interdepartmental consensus on which pain scale to use was also more likely. These findings are consistent with reports that a specialised approach to pain increases staff awareness and improves how pain is assessed and recorded . Our finding that slightly more than half of the hospitals with specialised services continued to use separate records, may be attributable to the pain specialists’ lack of access to other departments’ records.…”
Section: Discussionsupporting
confidence: 92%
“…Regular assessment was significantly higher in APS/APMP hospitals, where interdepartmental consensus on which pain scale to use was also more likely. These findings are consistent with reports that a specialised approach to pain increases staff awareness and improves how pain is assessed and recorded . Our finding that slightly more than half of the hospitals with specialised services continued to use separate records, may be attributable to the pain specialists’ lack of access to other departments’ records.…”
Section: Discussionsupporting
confidence: 92%
“…These studies include a critical review by Werner et al of outcome data from over 84,000 post-operative patients 37 , an analysis by Stadler et al which identified a cost-effective improvement in post-operative pain and morbidity 39 , and a study by Tighe et al which demonstrated that the introduction of an APS improved inpatient perception of pain relief upon return of consciousness after anesthesia and for 2 days post-operatively 40 . One indirect contributory factor to improving pain management and providing more adequate treatment 41,42 may be that an APS increases health professionals' pain awareness, exemplified by more frequent pain assessment and improved pain documentation 43 , although some clinicians have suggested that this could focus patients' attention on the issue.…”
Section: Acute Pain Servicesmentioning
confidence: 99%
“…10,24,25 Acute pain service teams may improve postoperative pain management, facilitate a possible reduction in postoperative nausea and vomiting, prevent the development of side effects, increase patient satisfaction, and decrease hospital stay. 10,15,[26][27][28][29][30][31] Studies show that there is considerable variation in the organization and procedures of APS teams. 22,24,32,33 Currently, there is no consensus about standards for staffing, specific facilities, procedures, and criteria on what constitutes a good APS.…”
Section: Introductionmentioning
confidence: 99%